Multicystic Higroma Colli: Case Report - Alfaina Wahyuni; Delarosa Ivana Melanita Anjani; Ichsanuddin Rizky Verifianto (CV. Inara, 2026)
Introduction: Cystic hygroma is a congenital disorder in the form of a cyst filled with lymphatic fluid arising from abnormalities in the embryonic development of the lymphatic system. Cystic Hygroma typically manifests in the neck area (75-90%) with; 20% in the axillae, 5% in the mediastinum, retroperitoneal region, and can also be in the thoracic wall. Cystic hygromas are often associated with chromosomal aberrations such as Trisomy syndrome; 21, 18, and 13, and Turner syndrome (45, X0). It can also be associated with cardiac anomalies and nonimmune hydrops fetalis. Cystic hygromas can usually be seen on sonographic examinations during the first trimester. Generally, these lesions are associated with a poor prognosis, especially if there is an abnormal karyotype. Reported a case of cystic hygroma colli in a woman who was pregnant at 18 weeks' gestation. In this case, termination of pregnancy was performed at 22 weeks of gestation. Fetuses with cystic hygromas have a high risk of poor outcomes. Therefore, once the diagnosis has been established, it is necessary to consider terminating the pregnancy. This case report demonstrates the importance of routine pregnancy evaluation. Finding the exact cause also needs to be done to avoid recurring events in subsequent pregnancies.